INVESTIGATING THE IMPACT OF LITHIUM MINING ON SOIL QUALITY, AND PLANT GROWTH IN ANGWA-KEDE COMMUNITY, KOKONA LGA, NASARAWA STATE, NIGERIA - EBIKEMEFA EBIMOBOWEI CLINTON; RAMALAN ALIYU MOHAMMED; DUNGKA THOMAS (Innovare Journal of Social Sciences, 2024)
Transition to green energy has made lithium mining one of the biggest venture in the world but this comes with its implications. This research was conducted to check the level of lithium mining contamination on soil quality and on plant in Angwa-Kede community due to observed poor agricultural yield. A systematic sampling method was conducted on both plant and soil samples from mining site and host community of Angwa-Kede to check the effects of lithium mining activity. The obtained plant and soil samples were analyzed using X-ray flourescence analysis (XRF) analysis to check elemental composition and the nutrient dynamics of both plant and soil. The XRF result revealed that soil samples from host community displayed higher level of Aluminum (Al) concentration in soil ranging from 20.48 to 31.18% Al indicating high contamination. Flame test results of plant samples from lithium mining site contains 0.466–0.477 ppm Li while those from host community has lithium concentration ranging from 0.0139 to 0.194 ppm Li which is above the accumulated level of lithium concentration in the blood (0.01374–0.02748 ppm Li) an indication of toxicity to human health. Soil samples of the mining site having risk factor (Rf) of 139.76, 168.49, and 350.26 while the soil samples from the host community has Rf of 7,194.24, 10,810.81, and 14,388.48, respectively. In conclusion, the obtained result shows high level of soil and plant lithium contamination in Angwa-Kede community which is caused by uncontrolled lithium mining method and poor waste disposal system.